CONFUSING THE MASK WITH THE FACE: THE CONCEPT OF “CELLULOID LIFE” IN VIDAS DE CELULOIDE. LA NOVELA DE HOLLYWOOD (1934) BY ROSA ARCINIEGA - Aquino Ramírez, Marlon Ytalo (2026)
This article offers an analysis of the concept of “celluloid life” raised in the novel Vidas de celuloide. La novela de Hollywood (1934) by the Peruvian writer Rosa Arciniega (Áncash, 1903 – Buenos Aires, 1999). It is based on the thesis that this work represents through narrative fiction the characteristics of an ancient phenomenon exacerbated by the massification of Hollywood cinema: the falsification of real public life. In that sense, the so-called “celluloid life” has various characteristics that, as stated in Arciniega’s novel, lead to the moral and physical self-destruction of the subject. Among these characteristics are its hyperdependence on advertising discourse, its inevitable submission to the gaze of others, its commercial transitoriness, and its need for validation with factual discourses. Through a hermeneutic-literary analysis with a comparative approach, it is concluded that this “celluloid life” and the risks arising from it constitute direct antecedents of contemporary issues related to the formation of identities in the digital world.